Tumor suppressor XAF1 induces apoptosis, inhibits angiogenesis and inhibits tumor growth in hepatocellular carcinoma - Zhu, Li Ming (Impact Journals LLC, 2014)
X-linked inhibitor of apoptosis (XIAP)-associated factor 1 (XAF1), a XIAP-binding protein, is a tumor suppressor gene. XAF1 was silent or expressed lowly in most human malignant tumors. However, the role of XAF1 in hepatocellular carcinoma (HCC) remains unknown. In this study, we investigated the effect of XAF1 on tumor growth and angiogenesis in hepatocellular cancer cells. Our results showed that XAF1 expression was lower in HCC cell lines SMMC-7721, Hep G2 and BEL-7404 and liver cancer tissues than that in paired non-cancer liver tissues. Adenovirus-mediated XAF1 expression (Ad5/F35-XAF1) significantly inhibited cell proliferation and induced apoptosis in HCC cells in dose- and time- dependent manners. Infection of Ad5/F35-XAF1 induced cleavage of caspase -3, -8, -9 and PARP in HCC cells. Furthermore, Ad5/F35-XAF1 treatment significantly suppressed tumor growth in a xenograft model of liver cancer cells. Western Blot and immunohistochemistry staining showed that Ad5/F35-XAF1 treatment suppressed expression of vascular endothelial growth factor (VEGF), which is associated with tumor angiogenesis, in cancer cells and xenograft tumor tissues. Moreover, Ad5/F35-XAF1 treatment prolonged the survival of tumor-bearing mice. Our results demonstrate that XAF1 inhibits tumor growth by inducing apoptosis and inhibiting tumor angiogenesis. XAF1 may be a promising target for liver cancer treatment.